Evaluation of association between parameters related to penetration into cerebrospinal fluid and the microbiological efficacy of vancomycin in patients with bacterial meningitis. (3rd April 2022) - Ishikawa, Masayuki; Uchida, Masashi; Yamazaki, Shingo; Shiko, Yuki; Kawasaki, Yohei; Suzuki, Takaaki; Iwadate, Yasuo; Ishii, Itsuko
Abstract: Vancomycin (VM) is used as empirical therapy for bacterial meningitis (BM). We investigated the relationship of the microbiological efficacy of VM for BM with VM minimum inhibitory concentration (MICVM ), serum VM trough concentration (VMser ) and cerebrospinal fluid (CSF) protein (P)/serum albumin (SA) ratio, which may reflect the extent of blood–brain barrier (BBB) disruption. Twelve BM patients were enrolled and VM was microbiologically effective in seven (58.3%). VMser, MICVM, and CSF-P/SA ratio were not associated with the microbiological efficacy of VM. The microbiological efficacy of VM was significantly associated with CSF-P/SA ratio multiplied by VMser relative to the MICVM (η = 0.61, p = 0.04). These results indicate that the parameter combining VMser, MICVM, and the extent of BBB disruption could be associated with the microbiological efficacy of VM in BM patients.